The Doctrinal Opinions Mulla Ali al- Qari in the Issues of Faith (Presentation and Criticism) - Siedazimov, Alisher (Journal of Islamic Sciences, 2019)
This Dissertation talks about Mullah Ali El Kary، died in (1014 hijri)، who is considered as one of the Hanfy scholars، who had a great effect on our Muslim Nation’s heritage، wit lot of attributions in various fields of science. He fell to some discrepancies in some believes. Thus this Dissertation is intended to demonstrate his true fact through studying his jurist’s opinions in Iman issues، so the reader can recognize how close or how deviated he was from Ahlu Sunnah Wal Jama regarding these issues. This research is consisted of 5 demands preceded by the above- mentioned Dissertation Abstract and followed with the recommendations and indexes. The Dissertation Abstract is intended for the research and results، while the Dissertation introduction is intended for the research issues The first demand is: Mullah Ali El Kary in the definition of Faith (Iman)، the second demand is about Mullah Ali El Kary opinions regarding the increase and decrease of Iman، while the third demand is about Mullah Ali El Kary opinions regarding the exclusion of Iman، and the fourth demand is about Mullah Ali El Kary opinions regarding the conflict of whether the Iman is only verbal or moral، the last demand is about Mullah Ali El Kary opinions regarding the deference between Islam and Iman. The concluded results of the Dissertation: The diseased Mullah Ali El Kary agreed with Ahlu Sunnah Wal Jama on the execlusion of Iman، but disagreed with them regarding the definition of Iman، stating that Iman do not increase or decrease and that Islam and Iman are the same thing and the dispute between Ahlu Sunnah Wal Jama and the Postponers regarding Iman issues is only verbal.